New benzoic acid derivatives from Cassia italica growing in Saudi Arabia and their antioxidant activity - Rwaida A. Al-Haidari; Mai M. Al-Oqail (Elsevier, 2020)
Two new benzoic acid derivatives: 1-p-hydroxy benzoyl-3-palmitoyl glycerol (1) and 6 -p-hydroxy benzoyl daucosterol (2), along with scutellarein-6-methyl ether (3), quercetin (4), and rutin (5) had been separated from Cassia italica (Fabaceae) aerial parts from EtOAc fraction. Their characterisation was accomplished by various spectroscopic techniques and by comparing with the published data. The Ethyl acetate (EtOAc) fraction and compounds 1-5 had been assessed for their antioxidant potential utilizing DPPH assay. They had significant antioxidant capacities with activity ranged from 19.7 to 95.8%, in comparison to butylated hydroxyanisole (BHA) (93.8%). These findings could provide a further evidence to support the traditional use of C. italica for the treatment of chronic or degenerative illnesses.